Synthesis of hydroxyapatite crystals using amino acid-capped gold nanoparticles as a scaffold - Rautaray, D.; Mandal, Sujata; Sastry, M. (Langmuir, 2005)
Inorganic composites are of special interest for biomedical applications such as in dental and bone implants wherein the ability to modulate the morphology and size of the inorganic crystals is important. One interesting possibility to control the size of inorganic crystals is to grow them on nanoparticles. We report here the use of surface-modified gold nanoparticles as templates for the growth of hydroxyapatite crystals. Crystal growth is promoted by a monolayer of aspartic acid bound to the surface of the gold nanoparticles; the carboxylate ions in aspartic acid are excellent hinging sites for Ca2+ ions. Isothermal titration calorimetry studies of Ca2+ ion binding with aspartic acid-capped gold nanoparticles indicates that the process is entropically driven and that screening of the negative charge by the metal ions leads to their aggregation. The aggregates of gold nanopartictes are believed to be responsible for assembly of the platelike hydroxyapatite crystals into quasi-spherical superstructures. Control experiments using uncapped gold nanoparticles and pure aspartic acid indicate that the amino acid bound to the nanogold surface plays a key role in inducing and directing hydroxyapatite crystal growth.